2018
DOI: 10.1007/s12035-018-1185-7
|View full text |Cite
|
Sign up to set email alerts
|

DHA Selectively Protects SAMP-8-Associated Cognitive Deficits Through Inhibition of JNK

Abstract: A potential role of marine n-3 polyunsaturated fatty acids (ω-3 PUFAs) has been suggested in memory, learning, and cognitive processes. Therefore, ω-3 PUFAs might be a promising treatment option, albeit controversial, for Alzheimer's disease (AD). Among the different mechanisms that have been proposed as responsible for the beneficial effects of ω-3 PUFAs, inhibition of JNK stands as a particularly interesting candidate. In the present work, it has been studied whether the administration of two different PUFAs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 73 publications
1
5
0
Order By: Relevance
“…The inhibition of JNK stands as an important mechanism responsible for the beneficial effects of ω-3 PUFAs. In a recent study by Vela et al, DHA was shown to inhibit cognitive deficits in a mouse model of AD through this mechanism [76] and several polyphenols, including CUR, were also shown to be potent JNK inhibitors [77,78]. In the present study, a significant increase of JNK2 phosphorylation was observed in J20 mice, which was abolished in CURDHA-ME-treated animals (Figure 6C).…”
Section: Discussionsupporting
confidence: 72%
“…The inhibition of JNK stands as an important mechanism responsible for the beneficial effects of ω-3 PUFAs. In a recent study by Vela et al, DHA was shown to inhibit cognitive deficits in a mouse model of AD through this mechanism [76] and several polyphenols, including CUR, were also shown to be potent JNK inhibitors [77,78]. In the present study, a significant increase of JNK2 phosphorylation was observed in J20 mice, which was abolished in CURDHA-ME-treated animals (Figure 6C).…”
Section: Discussionsupporting
confidence: 72%
“…To our knowledge, only one study investigated the association between serum DHA levels and Aβ positron-emission tomography (PET) imaging, and reported an inverse correlation with brain Aβ load (8). Although even less is known, DHA could also additionally contribute to the inhibition of tau phosphorylation (9). Finally, the beneficial effects of ω-3 PUFA on cognition have been most often seen in cognitively healthy individuals or individuals with mild cognitive impairment (MCI) (10).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a prospective human study showed that the intake of DHA, the precursor of MaR1, significantly reduced the incidence of AD [125,126]. On the other hand, there are reports that while DHA treatment improved memory impairment in mice, MaR1 treatment did not [127,128]. Considering that ω-3 PUFAs were effective only in addressing MCI and not advanced AD [103][104][105], it is necessary to elucidate the mechanism by which DHA is metabolized into MaR1 and the biochemical relationship between MaR1 and its receptor.…”
Section: Npd1 Gpr37mentioning
confidence: 99%